PENGARUH STRUKTUR AUDIT, PROFESIONALISME, DAN PENERAPAN TEKNOLOGI INFORMASI TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI MEDAN - Novita, Herlina; Sinambela, Marlina F; Pangaribuan, Maria U; Siahaan, Lilia S (Aksara Public, 2019)
The purpose of this research is to know how the influence of audit structure, professionalism and application of information technology to the performances of auditors. This research was conducted in the office of public accountant (KAP) registered at Indonesian Institute of Accountants (IAPI) area of Medan and use 65 auditors as samples. Analysis techniques use multiple linear regression and hypothesis testing with t-test and F-test. Data using is primary data and obtained by distributing questionnaire. The conclusions of research show that: 1) audit structure has an influence on auditor performance; 2) professionalism has no influence on auditor performance; 3) information technology Application has no effect on auditor performance; 4) audit structure, profesionalism and application of information technology have an effect on the performance of auditors.